Association of stress and depression with chronic facial pain: A case-control study based on the Northern Finland 1966 Birth Cohort. Issue 3 (4th May 2017) - Nevalainen, Netta; Lähdesmäki, Raija; Mäki, Pirjo; Ek, Ellen; Taanila, Anja; Pesonen, Paula; Sipilä, Kirsi
Abstract : Objective: The aim was to study the association between stress level and chronic facial pain, while controlling for the effect of depression on this association, during a three-year follow-up in a general population-based birth cohort. Methods: In the general population-based Northern Finland 1966 Birth Cohort, information about stress level, depression and facial pain were collected using questionnaires at the age of 31 years. Stress level was measured using the Work Ability Index. Depression was assessed using the 13-item depression subscale in the Hopkins Symptom Checklist-25. Three years later, a subsample of 52 subjects (42 women) with chronic facial pain and 52 pain-free controls (42 women) was formed. Results: Of the subjects having high stress level at baseline, 73.3% had chronic facial pain, and 26.7% were pain-free three years later. The univariate logistic regression analysis showed that high stress level at 31 years increased the risk for chronic facial pain (crude OR 6.1, 95%, CI 1.3–28.7) three years later. When including depression in a multivariate model, depression associated statistically significantly with chronic facial pain (adjusted OR 2.5, 95%, CI 1.0–5.8), whereas stress level did not (adjusted OR 2.3, 95%, CI 0.6–8.4). Conclusion: High stress level is connected with increased risk for chronic facial pain. This association seems to mediate through depression.